An AIEgen as an Intrinsic Antibacterial Agent for Light‐Up Detection and Inactivation of Intracellular Gram‐Positive Bacteria. Issue 24 (8th August 2021) - Dai, Tianjiao; Guo, Bingpeng; Qi, Guobin; Xu, Shidang; Zhou, Cheng; Bazan, Guillermo C.; Liu, Bin
Abstract: Infections caused by Gram‐positive bacteria, especially those able to invade and survive in host cells, threaten human health severely. It is therefore highly desirable to develop therapeutics that can selectively target and kill intracellular Gram‐positive pathogens with minimal toxicity to host cells. Herein, it is described that the aggregation‐induced emission luminogen (AIEgen) TPEPy‐Et, containing a positively charged pyridinium group and a hydrophobic tetraphenylethylene fragment, is effective for Gram‐positive bacteria detection and elimination. The fluorescence of TPEPy‐Et is greatly enhanced after incubation with Gram‐positive bacteria, which can be used to detect and trace the bacteria in cells. TPEPy‐Et also shows excellent killing effects against both extracellular and intracellular Gram‐positive bacteria through a membrane depolarization mechanism. The luminescent antibacterial agent TPEPy‐Et is thus promising for diagnosis and therapy against intracellular bacterial infection. Abstract : A luminogen with aggregation‐induced emission characteristics is developed for light‐up detection and elimination of intracellular Gram‐positive bacteria. The fluorescence of the AIEgen can be turned on upon incubation with Gram‐positive bacteria which allows bacteria detection. The AIEgen shows intrinsic bactericidal effect against both extracellular and intracellular Gram‐positive bacteria through membrane depolarization mechanism.